PROMOTING AUTONOMOUS LEARNING THROUGH' HOT POTATO E :" - Gendroyono (Eltics Journal PBI UPY, 2014)

(untitled)
This study was designed to investigate the role of 'Hot Potatoe5!in 5- - .flr autonomous learning of the English education students at Muhammadiyah Un:'.,- Yogyakarta. This study was conducted on some reasons: first, autonomous leamlr= significant in the success of leamers'leaming, and to make the learners l:.,-::: autonomous learning is quite tricky. Second, the use of Hot Potatoes as the sofhr',:: r'' simple and fun to publish any educat:ion materials online, and as a result, the studen:: I program. Therefore, it is very challenging for the teacher to find a way to : - , autonomous learning to the sfudents through the use of a simple education soft'"tar: -- 'Hot Potatoes' . The studywas aimed at exploring the roles of Hot Potatoes in English teaci-"-- -:r, learning. Fufther, it also explored the advantages of the Hot Potatoes in develop.- : , students' ability or habit in having autonomy in their learning. This research was a quah:, case study in nature since it dealt with a holistic description. The setting of the researci. - Muhammadiyah University of Yogyakarta with 10 students who have implernentec - Potatoes in designing teaching materials for them to use at schools. The procedure to c,:. ; the data was through questionnaires and interviews with the parlicipants. In analyzin. " data. the researcher first categorized the data gained from the questionnaires and -:, extracted the information from the data collected through the interview process. The . u.ere then grouped into categories and interpreted in accordance with the research questi. The study found that students first had awareness to be better in mastering En-- due to their online publishing the teaching materials developed with Hot Potatoes. Thel ' -- aware that by publishing materials online, people all around the globe would have a char:: stop by and read the materials. This awareness led them to learn by themselves or . grammar of the sentences they wrote. As a result, they starled looking up grammar boo,., check if the grammar was appropriate or not. The same process also happened to the c:.. of words and the spelling of rvords used in the teaching materials they developed. - - , checked and rechecked until they were sure of the correctness of the dictions and the sp.'- -* The last but not least is about the cultural issue in the sentences. It dealt wit]: .: appropriateness ofthe sentences they make due to native speakers'cultural backgrc--. Therefore, the writer concluded that the use of ,F1ol Potatoes promoted autonomy in sflid; . learrring. Keywords: Autonomous learning, Hot Potatoes, Students' Awareness, online publishin: